Optimistic and Positivity Biases in Employee Ratings: Empirical Evidence from Professional Soccer - Steffen Merkel; Sascha L. Schmidt; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2015)
This study uses a real case from professional soccer to examine intertemporal rating errors in performance appraisals. Motivated by research that extends the (prospective) optimistic bias and (retrospective) positivity bias to others, we formulate five hypotheses on the reflection of these biases in employee ratings and on rater-/ratee-related moderators of effect sizes. Employing unique assessment data for 164 players from a German Bundesliga club's youth academy, we show that the ratings of predicted and remembered performance are indeed higher than the talents' actual performance throughout a season. The differences depend positively on both the rater's experience and the amount of information available on the ratee but are not significantly influenced by the closeness of their relationship. Moreover, the (prospective) anticipation is even more positively biased than the (retrospective) recollection of the players' performance, which highlights an interesting asymmetry between looking forward and backward. Because the academy's appraisal and promotion schemes resemble typical company practices, we subsequently transpose our new understanding of rating errors – especially their intertemporal nature – to the business domain, suggesting practical implications for the design of corporate appraisal systems.
Keywords: 330; optimistic bias; positivity bias; rating error; performance appraisal; professional soccer